Low back disorders evidence-based prevention and rehabilitation - McGill, Stuart 1957- (Human Kinetics, 2016)
"Low Back Disorders, Third Edition, presents a solid research foundation in back anatomy, function, and injury mechanisms. Internationally recognized low back specialist Stuart McGill guides readers through the assessment of low back pain to identify specific pain triggers that substantiate evidence-based prevention and rehabilitation approaches." -- Back cover